1987
DOI: 10.1038/ki.1987.282
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gastrointestinal absorption of aluminumin in uremic rats

Abstract: To investigate the possibility of enhanced gastrointestinal absorption of aluminum in uremia, we measured the urinary aluminum excretion of rats following an oral load of 11 mg aluminum. Rats, in which uremia had been established by the remnant kidney model, excreted 1.5 to 2.2-fold higher amounts of aluminum in their urine over a collection period of five days compared with their controls. Within this period of time up to 0.17 +/- 0.08% of the oral dose of aluminum was recovered in the urine of the uremic ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 42 publications
0
14
0
2
Order By: Relevance
“…This is in contrast with the present study, in which no correlation between bone lanthanum levels and the development of a mineralization defect could be demonstrated. The slightly higher lanthanum concentrations in the bone of CRF animals might result from minor differences in gastrointestinal absorption of the element related to the CRF (49) and/or from higher bone turnover in the hyperparathyroid rat. Excretion of lanthanum is known to occur mainly via the bile (~63% of 0.3-mg/kg intravenous dose of LaCl 3 in NRF rats) and not the kidney (50) (Shire Pharmaceutical Development, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast with the present study, in which no correlation between bone lanthanum levels and the development of a mineralization defect could be demonstrated. The slightly higher lanthanum concentrations in the bone of CRF animals might result from minor differences in gastrointestinal absorption of the element related to the CRF (49) and/or from higher bone turnover in the hyperparathyroid rat. Excretion of lanthanum is known to occur mainly via the bile (~63% of 0.3-mg/kg intravenous dose of LaCl 3 in NRF rats) and not the kidney (50) (Shire Pharmaceutical Development, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also found no significant increase in the Al content of the serum, liver, cerebral cortex, or femoral bone in Al(OH) 3 -treated rats when compared with the normal control rats despite 5 /6-nephrectomy . [24] . They orally administered A1C13 to rats with moderate to severe uremia and found no difference in the serum Al concentration between the rats with normal and reduced renal function, indicating that the remnant kidney eliminated Al to a nearly normal degree .…”
Section: Discussionmentioning
confidence: 95%
“…Normally, only small amounts of aluminum are absorbed in the gastrointestinal tract. However, an enhanced uptake of aluminum possibly due to low gastric pH, vitamin D depletion and iron deficiency, together with an impaired elimination is observed in renal failure [71, 72, 73, 74]. The ingestion of aluminum compounds together with citrate (e.g.…”
Section: The Many Faces Of Renal Osteodystrophymentioning
confidence: 99%